Staphylococcus aureus ST1 promotes persistent urinary tract infection by highly expressing the urease - Xu, Kai; Wang, Yanan; Jian, Ying; Chen, Tianchi; Liu, Qian; Wang, Hua; Li, Min; He, Lei (Frontiers in Microbiology, 2023)
Staphylococcus aureus (SA) is a relatively uncommon cause of urinary tract infections (UTIs) in the general population. Although rare, S. aureus-induced UTIs are prone to potentially life-threatening invasive infections such as bacteremia. To investigate the molecular epidemiology, phenotypic characteristics, and pathophysiology of S. aureus-induced UTIs, we analyzed non-repetitive 4405 S. aureus isolates collected from various clinical sources during 2008–2020 from a general hospital in Shanghai, China. Among these, 193 isolates (4.38%) were cultivated from the midstream urine specimens. Epidemiological analysis showed UTI-derived ST1 (UTI-ST1) and UTI-ST5 are the primary sequence types of UTI-SA. Furthermore, we randomly selected 10 isolates from each of the UTI-ST1, non-UTI-ST1 (nUTI-ST1), and UTI-ST5 groups to characterize their in-vitro and in-vivo phenotypes. The in-vitro phenotypic assays revealed that UTI-ST1 exhibits an obvious decline in hemolysis of human red blood cells and increased biofilm and adhesion in the urea-supplemented medium, compared to the medium without urea, while UTI-ST5 and nUTI-ST1 did not show significant differences between the biofilm-formation and adhesion abilities. In addition, the UTI-ST1 displayed intense urease activities by highly expressing urease genes, indicating the potential role of urease in UTI-ST1 survival and persistence. Further in-vitro virulence assays using the UTI-ST1 ureC mutant showed no significant difference in the hemolytic and biofilm-formation phenotypes in the presence or absence of urea in the tryptic soy broth (TSB) medium. In-vivo UTI model also showed that the CFU of UTI-ST1 ureC mutant reduced rapidly during UTI pathogenesis after 72 h post-infection, while UTI-ST1 and UTI-ST5 persisted in the urine of the infected mice. Furthermore, the phenotypes and the urease expression of UTI-ST1 were found to be potentially regulated by the Agr system with the change in environmental pH. In summary, our results provide important insights into the role of urease in S. aureus-induced UTIs pathogenesis in promoting bacterial persistence in the nutrient-limiting urinary microenvironment.